Deep-time organizations: Learning institutional longevity from history. (April 2020) - Hanusch, Frederic; Biermann, Frank
The Anthropocene as a new planetary epoch has brought to the foreground the deep-time interconnections of human agency with the earth system. Yet despite this recognition of strong temporal interdependencies, we still lack understanding of how societal and political organizations can manage interconnections that span several centuries and dozens of generations. This study pioneers the analysis of what we call "deep-time organizations." We provide detailed comparative historical analyses of some of the oldest existing organizations worldwide from a variety of sectors, from the world's oldest bank (Sveriges Riksbank) to the world's oldest university (University of Al Quaraouiyine) and the world's oldest dynasty (Imperial House of Japan). Based on our analysis, we formulate 12 initial design principles that could lay, if supported by further empirical research along similar lines, the basis for the construction and design of "deep-time organizations" for long-term challenges of earth system governance and planetary stewardship.